Satire Narrative of Environmental Issues in Jostein Gaarder’s The World According to Anna - Rahmawati Nur Azizah (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2018)
This paper aims to present of how climate problem and literature in Jostein Gaarder's The World According to Anna is portrayed, argued, and related to each other. Approaching through Ecocriticism, the result of the analysis shows that there are several environmental issues appearing in the novel. These are concerning oil vanishing, plant and animal extinction, drought and famine. Gaarder presents the environmental issues both in a satire and connects it with a political and economic system as well. Whereas Gaarder inclines to accept commonsense in Orientalism outlook in his way to describe the Middle East and Europe, the novel uses the Aladdin's letter and his ring in terms of the ethical messages. In such a way, both are considered as the inheritance to the next generation in an effort of preserving biological